Peran Pendampingan Desa Dalam Implementasi Undang-Undang Desa Di Jawa Tengah -Tahun 2018 - Suharto suharto (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2019)
Abstract Village Facilitation is an activity to carry out community empowerment actions through assistance, organization, direction and facilitation of the Village. Village facilitation in the framework of implementing Law Number 6 of 2014 concerning Villages is very important in determining its success. Seeing the current condition of the village which is very heterogeneous in terms of quantity, quality or capacity and even the potential of natural resources and human resources is very varied, the role of village assistance in the framework of implementing the Village Law is very important in helping villages implement the mandate of the Village Law. To find out more about the role of village assistance, in this study the problem is: "What is the role of village assistance in the context of the implementation of the Village Law in Central Java-2018 ?. Village Community Empowerment is an effort to develop community independence and prosperity by increasing knowledge, attitudes, skills, behavior, abilities, awareness, and utilizing resources through the determination of policies, programs, activities, and assistance in accordance with the essence of the problems and priorities of the needs of the village community. The objectives of assisting villages in Ministerial Regulation (Permendes No 3 of 2015) include: a. Increasing the capacity, effectiveness and accountability of village governance and village development; b. Increasing the initiative, awareness and participation of the Village community in participatory village development; c. Increase the synergy of inter-sectoral village development programs; d. Optimizing village local assets emancipatively. The Village Facilitator is assigned to assist the Village in organizing Village development and empowering the Village community in Central Java. Village Facilitators carry out the task of assisting Villages in the implementation of the Village Law in Central Java which includes: a. assist the Village in planning, implementing, and monitoring Village development and empowering the Village community; b. assist the Village in carrying out management of basic social services, development of the Village economic effort, utilization of natural resources and appropriate technology, construction of Village infrastructure, and empowerment of the Village community; c. conduct capacity building for the Village Government, Village community organizations in terms of development and empowerment of the Village community; d. organizing within village community groups; e. increase capacity for Village Community Empowerment Cadres and encourage the creation of new Village development cadres; f. assist the Village in participatory rural development; and g. coordinate assistance at the sub-district level and facilitate reports on the implementation of assistance by the Camat to the District / City Governments throughout Central Java.